Ukrainian Trade with Grains - Kuznietsov, Illia; Štěrbová, Ludmila, 1957-; Shymanska, Kateryna; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
Historical studies highlighted Ukraine's strategic agricultural significance, based on its fertile landscape, advantageous topography, and strong production capacity. Nonetheless, ongoing problems such as infrastructural constraints, market reliance, and unequal access to agricultural subsidies impede the complete realisation of potential. Following 2014, Ukrainian grain trade transitioned considerably towards European and alternative global markets, supported by crucial agreements such as the EU - Ukraine DCFTA, which greatly improved market integration and standards alignment. The beginning of the 2022 conflict sharply exposed Ukraine's weaknesses while simultaneously highlighting its resilience. Initial interruptions were significant, with Black Sea ports obstructed and exports substantially diminished. Innovative responses rapidly surfaced, including the creation of alternate logistics routes like the EU - supported “Solidarity Lanes,” Danube River channels, and new coastal marine corridors along NATO member state coastlines. These actions effectively mitigated certain economic and humanitarian repercussions, enabling export volumes to significantly rebound by late 2023 and into 2024. Comparative policy study from 2014 to 2023 revealed a notable transformation: transitioning from market-oriented reforms and EU integration to emergency wartime measures and strategic subsidy adjustments. Large agricultural estates have frequently gained significant benefits from subsidies. However, recent attempts have prioritised a more equitable distribution of support to smaller producers, along with broader EU trends. In contrast to structural weaknesses and external threats, particularly geopolitical instability and market volatility, a SWOT analysis highlighted Ukraine's grain trade's main advantages and opportunities, such as its geographic location, production capabilities, and continuous logistical innovations.
Long-term recovery and growth require sustained investments in technical innovation, market diversity, infrastructure resilience, and diplomatic engagement, according to strategic suggestions. In the end, this thesis shows how proactive international cooperation, adaptive logistics, smart policy interventions, and ongoing technical modernisation may help Ukraine's grain trading sector not just survive but grow in the face of difficulties.
Vedoucí práce: Ludmila Štěrbová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses